Trade, Foreign Direct Investment or Acquisition: Optimal Entry Modes for Multinationals - Theo Eicher; Jong Woo Kang (Center for Economic Studies and ifo Institute (CESifo), 2004)
We examine multinationals' optimal entry modes into foreign markets as a function of market size, FDI fixed costs, tariffs and transport costs. Our results highlight why large countries are more likely to attract acquisition investment, while intermediate-sized countries may be served predominantly through trade, even in the presence of high tariffs. Small countries are most likely to experience either FDI or no entry. We also show how these results vary with the competition intensity in the host country. FDI fixed costs, tariffs and transport costs are crucial not only in determining whether to engage in FDI or trade, but they are also shown to influence the acquisition choice as trade and FDI threats influence the acquisition price. Finally we explore the welfare implications of tariff reductions for both the local firm and the multinational and investigate political motives to impose endogenous tariffs that influence not only the welfare of a local firm, but also the entry mode of the multinational
Keywords: O00; 330